Anti-Parkinson drug biperiden inhibits enzyme acetylcholinesterase - Kostelník, Adam; Čegan, Alexander; Pohanka, Miroslav (My University, 2017)
Biperiden is a drug used in Parkinson disease treatment. It acts as antagonist of muscarinic receptor activated by acetylcholine. Acetylcholinesterase is an enzyme inhibited by various compounds, however there has not been proposed evidence about interaction with biperiden molecule. Therefore, we investigated this interaction using standard Ellman´s assay and experimental data were completed with in-silico prediction by SwissDock docking software. We revealed inhibition mechanism and inhibition constant was calculated to be 1.11 mmol/l; interaction of biperiden occurs in peripheral anionic subsite. Biperiden appeared to be very weak inhibitor but it can serve as a leading structure in a pharmacological research.
Biperiden inhibuje enzym acetylcholinesterasu
Keywords: Acetylcholinesterase; biperiden; inhibitor; docking; Acetylcholinesterasa; biperiden; inhibitor; docking